Assessment of Awareness, Knowledge, Attitudes, Practices, and Quality of Life Among Glaucoma Patients at a Tertiary Eye Hospital in Nepal - Gautam Adhikari, Pragati; Thapa, Madhu (Tribhuvan University Journal, 2026)
Glaucoma is one of the leading causes of irreversible blindness that affects patients' quality of life. Adequate awareness, knowledge, positive attitudes, and self-care practices play vital roles in treatment and preservation of visual function in glaucoma patients. This study aimed to assess the levels of awareness, knowledge, attitudes, and practices, and quality of life among diagnosed cases of primary open-angle glaucoma at a tertiary eye care centre in Nepal. A hospital-based cross-sectional study was conducted among 110 patients attending the glaucoma clinic. Data were collected using a structured KAP questionnaire and the Glaucoma Quality of Life-15 (GQOL-15) questionnaire. KAP scores were categorized based on percentage scores, and quality of life was assessed using total GQOL-15 scores. Associations between variables were analyzed using chi-square test, independent t-test, and one-way ANOVA, with a p-value